Paliperidone long-acting injection in the treatment of an adolescent with schizophrenia with fluctuating mental symptoms during menstrual period: a case report - Wang, Feng; Chen, Juan; Guo, Linglin; Li, Zhixiong; Li, Zhe (Frontiers in Psychiatry, 2023)
Background The treatment of schizophrenia, a chronic disabling psychiatric disorder, mainly relies on antipsychotics to control the disease and improve clinical symptoms. Various medication options are available, and differences in treatment effects, even for the same medication, have been noted. Treatment efficacy is correlated with the patient’s sex, age, and physical condition. When a drug fails to achieve the desired effect or the symptoms are unstable, the drug dose is often increased or a change in medication is advised according to the patient’s situation. Case presentation We report the case of a 16 years-old girl with schizophrenia and apparent psychotic symptoms. According to the genetic testing results, the symptoms were effectively controlled, and she was discharged from the hospital with the prescription of paliperidone sustained-release tablets. During the follow-up, her symptoms fluctuated during menstrual period, causing her great distress. Furthermore, her compliance gradually declined during the following 2 years of treatment, and the medication was often discontinued. We changed the drug from an oral tablet to an injection preparation while maintaining the active ingredients of the drug. The patient’s symptoms were significantly controlled, and no fluctuation of symptoms occurred during the menstrual cycle. Conclusion Long-acting antipsychotic injections can be administered to female adolescents with schizophrenia who experience fluctuating psychotic symptoms during menstruation. This technique can ensure both consistency of medication and improvement in clinical symptoms.